Small Molecule Suppression of Carbapenem Resistance in NDM-1 Producing Klebsiella pneumoniae - Worthington, Roberta J. (American Chemical Society, 2012)
[Image: see text] The already considerable global public health threat of multidrug-resistant Gram-negative bacteria has become even more of a concern following the emergence of New Delhi metallo-β-lactamase (NDM-1) producing strains of Klebsiella pneumoniae and other Gram-negative bacteria. As an alternative approach to the traditional development of new bactericidal entities, we have identified a 2-aminoimidazole-derived small molecule that acts as an antibiotic adjuvant and is able to suppress resistance of a NDM-1 producing strain of K. pneumoniae to imipenem and meropenem, in addition to suppressing resistance of other β-lactam nonsusceptible K. pneumoniae strains. The small molecule is able to lower carbapenem minimum inhibitory concentrations by up to 16-fold, while exhibiting little bactericidal activity itself.